Homozygosity for Robertsonian Translocation (14q;15q) in a Newborn with a Familial History of Recurrent Abortion and Newborns Affected by Hepatosplenomegaly: A Case Report - Sahraeean, Sahra; Jebelli, Asiyeh; Shahbazi, Zahra; Piryaei, Fahimeh (Journal of Reproduction & Infertility, 2023)
Background: Robertsonian translocations (RobTs) are one of the major chromosomal abnormalities which lead to spontaneous abortion. They occur in the human population at the rate of 1 in 1000 live infants. In this paper, a family carrying one of the rare RobTs was presented and some features of all kinds of RobTs were reviewed. Case Presentation: A couple with a history of three miscarriages was referred to Omid Health Clinic of Hamadan, Iran. The karyotype of the woman was 45,XX, rob(14;15)(q10;q10) and she exhibited phenotypically good health. Karyotype analysis of proband’s uncle and his wife with a consanguineous marriage revealed that they were both carriers of rob(14;15). This couple had six offspring, three of which were dead, and the other three were alive with a normal phenotype. Besides, this couple had an unborn child, with a karyotype of 44,XX,rob(14;15)(q10;q10). Conclusion: These observation showed that genetic counseling, pedigree, and chromosomal analysis are needed to discover the cause of spontaneous abortion, stillbirth, congenital anomalies, sudden infant death syndrome (SIDS), etc. Moreover, families carrying RobTs would be offered prenatal diagnosis screening tests and, if necessary, assisted reproductive technology methods to assist with preimplantation genetic test for structural rearrangement (PGT-SR) reproduction.